EEC law - Parry, Anthony; Hardy, Stephen T. (London ; New York : Sweet and Maxwell ; M. Bender, 1973)
The book is divided into eight parts and thirty eight chapters.
Includes index.
Bibliography: p. 479-493.
osc 08/11/2018
Loans
Keywords: Law